(untitled) (Journal of Informatics and Mathematical Sciences, 2018)
The present work considers the possibility of using river currents to generate electric power in order to supplement existing power units. A physical system consisting of a flowing river/canal with rectangular cross section, an open channel nozzle, and an impact turbine is modelled mathematically. The model is simulated using MATLAB for varying slopes and two nozzle-turbine sequences. It is found that the usage of nozzles demonstrably increases the velocity, and therefore, the kinetic energy of the flow. A total power ranging from 0.34 to 10.79MW for the lowest and highest value of slope, respectively, is predicted by the model. Possible applications are discussed.